Fikih Pluralisme dalam Perspektif Ulama NU - Fathorrahman Fathorrahman (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2015)
In the life of the nation which Seara essentially based on the principle of diversity, pluralism happenings become very important idea to be actualized. This, considering the many phenomena of social groups, especially those based on the religious, who plays more the majority of much use repressive means to memaksanakan belief to more minority groups. Inevitably, the consequences of action anarchism became a partial continuation of the way of thinking that the minority must follow the majority. Ironically, about pluralism which can be used as a spirit of togetherness and mutual respect, to be one shot stigma that pluralism is understood that contrary to religious teachings tertentu.Seiring with the stigma, the Indonesian Ulema Council (MUI) had issued a fatwa for pluralism .Implikasinya, this fatwa increasingly confirmed as an excuse to strengthen joints to discredit the majority of minorities, particularly the different streams and ideology with groups such mayoritas.Namun, fortunately lah is a collection of scholars who are members of the Nahdlatul Ulama (NU), which has the attitude and stance Different, which still considers pluralism as values of divinity and the human values that should dilestarikan.Sehingga, many generations NU, especially at lower levels, which fosters mutual respect in tengarah diversity that unfolded in this sphere of life them.And , can not be separated from the elders thought NU clerics such as Gus Dur, Mustafa Ali Jacob, Ali Yafie, and others are introducing religious teachings of the tolerant, moderate, balanced, and berkeadilan.Untuk know more detail and depth about how to construct ideas NU scholars in response to the spirit of pluralism absolute maintained and how the position of NU in the treatment of minority groups, this paper tries to break them down further.